Comparative transcriptome analysis reveals the growth and development in larval stages of the swimming crab Portunus trituberculatus - Chen, Jiameng; Chen, Xiayue; Mu, Changkao; Wang, Chunlin; Ye, Yangfang; Li, Ronghua; Song, Weiwei; Shi, Ce; Liu, Lei; Wang, Huan (Frontiers in Marine Science, 2023)
Portunus trituberculatus, an economically important marine crab widely distributed along the coast of China, has been in short supply of high-quality crab seedlings in recent years. Many biological processes are regulated during the larval development of P. trituberculatus. These regulations occur at different biological levels, particularly involving gene expression in larval developmental processes. Understanding the changes in these critical genes can help further regulate these biological processes to increase crab seedlings’ survival and improve crab seedlings’ survival quality. In this study, we investigated the molecular mechanisms of morphological and physiological changes in larval stages of P. trituberculatus with the microarray technique. A total of 109533 unigenes were obtained, of which 16 genes were differentially expressed during the whole development stages with evident timeliness. The enrichment analysis and comparison of differentially expressed genes (DEGs) showed three types of physiological activities, chitin development, energy metabolism and neuroendocrine development. The physiological activities were evident in the early development of P. trituberculatus, especially at the Z4-M stage, which is crucial for the growth and development of crab larvae. Among these DEGs, cuticle proteins, retinol dehydrogenase (RDHs), Juvenile Hormone Epoxide Hydrolase (JHEH), and other vital genes were differentially expressed at the Z4-M stage. Moreover, the insulin-like androgenic gland (IAG), which was reported to be associated with sex differentiation, was highly expressed in the megalopa stage, indicating that the gender divide may be about to begin at this stage. Overall, this research provides a theoretical basis for the development of swimming crab larvae, which helps promote the artificial growing seedlings technology of P. trituberculatus.